Zu den Anfängen der tschechoslowakisch-polnischen Beziehungen - Karel Schelle (Journal on European History of Law)
This article examines the complex situation in Silesia regarding public administration and the international resolution of the "Teschener Problem" due to national and political conflicts. The Landesnationalausschuss für Schlesien and the Polish Krajowa Rada Narodowa w Cieszynie could not handle the situation independently. Efforts were made to limit the authority of the Landesnationalausschuss, leading to its diminishing involvement in resolving the Teschener Problem. Both sides sought external intervention, with the Landesnationalausschuss requesting military occupation by the Czechoslovak or Entente armies and the Polish side continuing efforts to annex Teschen. The situation intensified after the Polish government declared jurisdiction over Teschener Land. Various diplomatic efforts were made, including appeals to the Entente powers and negotiations between the Czechoslovak and Polish governments. The conflict escalated into a seven-day war, with the Czechoslovak army pushing Polish forces back to the Vistula River. However, the Entente powers did not support the establishment of a fait accompli. Eventually, the dispute was referred to the Botschafterkommission, and on July 29, 1920, a decision was announced that favoured Czechoslovakia. The international commission took over the administration, and the Czechoslovak military and gendarmerie were deployed to restore order. The Hlučínsko region was incorporated into Czechoslovakia, and the political district administration was established. The situation gradually normalised, but the consequences of the Teschener Problem had a lasting impact on Czechoslovak-Polish relations and the residents of Silesia.